Engineered testbeds for investigating syringe injection performance in human factors studies - Andrew Pack; Sabrina Su; Frank A. Drews; Amrish Chourasia; Kevin Cluff; Joy Guerrieri; Jungkyu Kim (Human Factors in Healthcare)
Objective: We aimed to develop two injection testing systems to allow future work to measure the dynamic performance of injections using prefilled syringes across different fluid viscosities. Background: Subcutaneous (SC) injections, delivered into adipose tissue, are a convenient and cost-effective method of administering medications. However, administration via syringes can pose physical ergonomic challenges as the medication viscosity increases. Methods: To investigate the relationship between applied force and fluid viscosity, we constructed two testing systems: a passive system using prefilled syringes containing fluids of different viscosities and an active system that simulates different fluid viscosities by adjusting the cross-sectional area of a tube to modulate fluidic resistance. Both systems record the force exerted on the syringe plunger. Results: Results from data collection using a syringe pump with solutions of 5, 10, 15, and 20 centipoise (cP) revealed a polynomial relationship between viscosity and force, contrary to the expected linear relationship. This unexpected pattern likely resulted from complex fluid dynamics in the 27-gauge needle. Testing of both systems confirmed that fluidic resistance control through viscosity and resistance effectively captured injection profiles. User testing further supported these findings. Conclusion: The test systems provide valuable insights into the complex interplay between fluid viscosity, applied force, and syringe characteristics. Application: These findings can inform future syringe design, needle gauge selection, and help establish upper viscosity limits for SC injectable medications. The presented systems offer valuable tools for future Human Factors studies, enabling quantification of user strength during syringe injections across various groups, including those with hand impairments. Précis: Two novel testing systems mimicking variable viscosity injections through fluidic or mechanical property variation enable the quantification of user strength in Human Factors studies and inform syringe design and viscosity limits.